Theoretical and methodical bases of pendulum migrations and analysis of the sources of intra-regional flows of population movements (for example, Transcarpathion region, Ukraine) (Vallis Aurea, 2015)
The scientific article analyses theoretical fundamentals of commutation in the region from rural to urban areas, highlights its main reasons and examines some aspects of pendulum migration in the region. Both positive and negative consequences of the commutation of the population have been studied. The present population size and the scale of arrival and departure of the population in the context of natural economic areas of Transkarpathion region have been analyzed.